Characterizing minimal impartial rules for awarding prizes - Shohei Tamura (Osaka University, Institute of Social and Economic Research (ISER), 2015)
We study the problem of choosing prize winners from among a group of experts when each expert nominates another expert for the prize. A nomination rule determines the set of winners on the basis of the profile of nominations; the rule is impartial if one's nomination never influences one's own chance of winning the prize. In this paper, we consider impartial, anonymous, symmetric, and monotonic nomination rules and characterize the set of all minimal such ones. We show that the set consists of exactly one nomination rule: a natural variant of the plurality correspondence called plurality with runners-up.
Additional information: The 17th ISER-Moriguchi Prize (2014) Awarded Paper.
Keywords: D63; D71; 330; Institutional design; Award rule; Conflict of interest; Impartiality; Plurality correspondence